The psychological impact of the pandemic: the effects of COVID-19 pictures on emotional processing - Ribatti, Raffaella Maria; Curci, Antonietta; Lanciano, Tiziana (Psychology Hub, 2022)
The impact of the COVID-19 pandemic continues to affect the lives of billions of people in recurrent waves. The present study aims to investigate the effects of exposure to COVID-related pictures on affective states, working memory performance, rumination, and intrusion. Negative emotions -- such as those aroused by the pandemic -- trigger a post-emotional elaboration depleting working memory resources required to perform other tasks. We expected a greater negative affect state, a greater impairment in working memory performance (as assessed by a visuospatial task), and a greater persistence of rumination and intrusion in participants exposed to COVID-19-related pictures as compared with emotional and neutral pictures. Results on a sample of 96 subjects show that when participants were requested to process COVID-19 pictures, their negative affective states increased over time (p<0.05), but the same does not hold for the emotional and neutral conditions. Furthermore, when participants were requested to process COVID-19 pictures, they exhibited a relevant persistence of long-term rumination (p<0.05), in particular in its deliberate form (p<0.05), and a significant persistence of intrusive thoughts (p<0.005). These considerations lead to serious concerns about post-event processing as a long-term consequence of the ongoing pandemic.